MicroRNA Mediate Visfatin and Resistin Induction of Oxidative Stress in Human Osteoarthritic Synovial Fibroblasts Via NF-κB Pathway - Sara Cheleschi (International Journal of Molecular Sciences, 2019)
Synovial membrane inflammation actively participate to structural damage during osteoarthritis (OA). Adipokines, miRNA, and oxidative stress contribute to synovitis and cartilage destruction in OA. We investigated the relationship between visfatin, resistin and miRNA in oxidative stress regulation, in human OA synovial fibroblasts. Cultured cells were treated with visfatin and resistin. After 24 h, we evaluated various pro-inflammatory cytokines, metalloproteinases (MMPs), type II collagen (Col2a1), miR-34a, miR-146a, miR-181a, antioxidant enzymes, and B-cell lymphoma (BCL)2 by qRT-PCR, apoptosis and mitochondrial superoxide production by cytometry, p50 nuclear factor (NF)-κB by immunofluorescence. Synoviocytes were transfected with miRNA inhibitors and oxidative stress evaluation after adipokines stimulus was performed. The implication of NF-κB pathway was assessed by the use of a NF-κB inhibitor (BAY-11-7082). Visfatin and resistin significantly up-regulated gene expression of interleukin (IL)-1β, IL-6, IL-17, tumor necrosis factor (TNF)-α, MMP-1, MMP-13 and reduced Col2a1. Furthermore, adipokines induced apoptosis and superoxide production, the transcriptional levels of BCL2, superoxide dismutase (SOD)-2, catalase (CAT), nuclear factor erythroid 2 like 2 (NRF2), miR-34a, miR-146a, and miR-181a. MiRNA inhibitors counteracted adipokines modulation of oxidative stress. Visfatin and resistin effects were suppressed by BAY-11-7082. Our data suggest that miRNA may represent possible mediators of oxidative stress induced by visfatin and resistin via NF-κB pathway in human OA synoviocytes.